Macrophage migration inhibitory factor in acute kidneyinjury - Du, Yiwei; Hao, Hao; Ma, Heng; Liu, Hongbao (Frontiers in Physiology, 2022)
Acute kidney injury (AKI) is a complex clinical syndrome with multiple etiologies and pathogenesis, in which pathophysiological mechanisms, such as oxidative stress, inflammatory infiltration, cell repair and proliferation, play a pivotal role in the occurrence and development of AKI. However, due to its limited early diagnosis and treatment methods, the life and health of patients are threatened by the high morbidity and mortality rate seriously. Recently, macrophage migration inhibitory factor (MIF) has received increasing attention owing to its pleiotropic protein molecule in acute organ injury. MIF，released into the peripheral circulation in large amounts when AKI occurs， is mainly expressed in renal tubular cells. It is found that the severity of AKI is tightly associated with the secretory level of MIF in clinical studies, whereas the concrete mechanism still remains enigmatic. Herein, we provide an overview on the biological role of MIF in the process of AKI and the clinical application prospects of MIF as a potential therapeutic target.